Subungual malignant melanoma – re-learning the lesson. (10th March 2011) - Amin, Kavit; Edmonds, Katy; Fleming, Andrew; Powell, Barry
Abstract : The authors present two patients referred by colleagues after traumatic hand injury. However, upon closer inspection, both patients had pigmented lesions under the nail bed, which upon biopsy showed proven subungual malignant melanoma. The authors wish to emphasise the importance of this diagnosis, especially in emergency care.